Web-based application architecture for attaining the society with desirable library collection - Shahrul Asari, Seri Intan Idayu; Bunawan, Ap-azli; Idris, Ahmad Sufi Alawi; Hussin, Nurussobah; Samsudin, Ahmad Zam Hariro (Universiti Teknologi MARA, Kedah, 2017)
Nowadays, interchange on library collection is vital aspect for libraries. As being practice, the inter-library loan aspect is conducted. However, the stated activity shows several issues until to date. The common issues that being raised by the society are on the urgency and duration of getting the collection. Moreover, as many procedures need to be followed, the urgency of having the collection is unoccupied. As to solve this issue, an alternatives process of sharing the collection is proposed. By inventing a web-based application on sharing the collection, it would reduce the duration of time request. The development of web-based need to be properly designed. As to initiate the development process, a dedicated architecture need to be designed at first. This is where this project is proposing to design an application architecture for collection exchanged. The architecture contains three (3) elements which include the visibility, efficiency and relevancy of the collection. The element of visibility would reflect the number of collection available in libraries. Meanwhile the efficiency relates to the amount of time required in finding the collection with the existence of the web. Last but not least the relevancy relates to the precision of the collection being listed in the web. The web would benefit the society by giving a well-structured platform that enhance the inter-library loan function. Thus, this is also can facilitate the urgency of having the collections as well as generates more efficient process of inter-library loan.